Selective Spinal Fusion for Lenke Type 5C Adolescent Idiopathic Scoliosis: Short Term Radiographic Follow Up. (Journal of Pakistan Orthopaedic Association, 2020)
Objective: To determine the short term radiological outcomes of Lenke type 5C adolescent idiopathic scoliosis in terms of Cobb angle correction and coronal balance after selective posterior segmental spinal instrumentation with pedicle screws.Methods: This retrospective cohort study was conducted in Department of Orthopedic and Spine Surgery Ghurki Trust Teaching Hospital/ Lahore Medical and Dental College Lahore. The medical records of patients from 17th April 2015 to 29th October 2019 who underwent selective spinal fusion with pedicle screws for Lenke type 5C adolescent idiopathic scoliosis were reviewed. Pre-operative radiographs were evaluated for Cobb angle of lumbar or thoracolumbar curve as well as sagittal and lumbar modifier on anteroposterior and lateral standing films. The curve correction, implant density, number of segment fused and coronal balance was assessed on post operative radiographs. The pre and post operative comparison of important study variables were done and P value was calculated with the help of Chi-square test. P value < 0.05 was considered statistically significant.Results: The total number of patients were 34. Majority (94.1%,n=32) were females while only 2(5.9%) were males. The mean age at the time of operation was 14.35±2.19 years (range 8 to 19 years). Mean pre-operative and post-operative Cobb angles were 61.790±13.120 (range 400 to 850) and 10.550±8.710 (range 00 to 300) respectively (P value 0.00). The mean percentage of curve correction and percentage of fulcrum flexibility was 83.35±13.07 % (range 55% to 100%) and 59.56%±15.07 (range 28.57% to 84.60%) respectively (P value 0.469). Mean implant density and fusion mass was 66.03±7.94% (range 53 to 79%) and 10.32±2.8 (range 7 to 15%) segments respectively. The coronal balance was achieved in all patients. No major complication was noted.Conclusion: Near normal Cobb angle correction and coronal balance was achieved in all patients of Lenke type 5C adolescent idiopathic scoliosis treated with posterior segmental spinal instrumentation utilizing pedicle screws.